Towards a theology of the concord of God: A Japanese perspective on the trinity - Miyahira, Nozomu; (1966-...) (U.K., 2000)
This book introduces a new Japanese theology and a unique Trinitarian formula based on the Japanese intellectual climate: three between-nesses and one concord. It also represents a new interpretation of the Trinity, a co-subordinationism, which is in line with orthodox Trinitarianism: every single person of the Trinity is eternally and equally subordinate (or serviceable) to the other persons.
Keywords: Japan -- Religion